Development of Geopolymers Composite Based on Metakaolin-Nano ZnO for Antibacterial Application. (March 2017) - Nur, Q A; Sari, N U; Harianti,; Subaer,
Abstract: A research on the development of geopolymers composite based on metakaolin-nano ZnO for antibacterial application has been conducted. The aim of this study was to investigate the influence of nano ZnO addition in the production of antibacterial composite. Nano ZnO was produced through precipitation of ZnSO4 in NaOH solution. The composites were developed through alkali activation of metakaolin added with nano ZnO at various concentrations, namely 5%, 10%, & 15% relative to the weight of metakaolin. The structure and the phase of the starting and the resulting materials were examined by using x-ray diffraction (XRD). The resulting composites were immersed in water taken from a well for several days to investigate their antibacterial properties. The morphology and the presence of bacteria on the surface of composites were investigated by using scanning electron microscopy (SEM). It was found that geopolymers composites based on metakaolin-nano ZnO is an effective composite to limit the growth of the bacteria.